2020
DOI: 10.1108/tr-05-2019-0166
|View full text |Cite
|
Sign up to set email alerts
|

Developing a customer loyalty model for guest houses in China: a congruity-based perspective

Abstract: Purpose Although the number of guest houses in China is increasing rapidly, many of them are not performing well in developing customer loyalty. Self-congruity and functional congruity represent two cost-effective but inadequately researched ways for guest houses to maintain customers. In view of the lack of empirical research explaining the post-purchase behavior of guest house customers, the purpose of this study is to develop a congruity-based customer loyalty model for this specialized type of accommodatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A very limited number studies of the homestay industry have adopted the concept of emotional solidarity to measure the perceived closeness of guests to their hosts [1,34,42]. Furthermore, although customer loyalty receives much academic attention in the homestay industry [83][84][85], the prediction of customer loyalty from the perspective of emotional solidarity is still lacking. Thus, this study complements the related research of adopting emotional solidarity theory in discussing the relationship between hosts and tourists to explain tourists' loyalty towards homestay industry.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…A very limited number studies of the homestay industry have adopted the concept of emotional solidarity to measure the perceived closeness of guests to their hosts [1,34,42]. Furthermore, although customer loyalty receives much academic attention in the homestay industry [83][84][85], the prediction of customer loyalty from the perspective of emotional solidarity is still lacking. Thus, this study complements the related research of adopting emotional solidarity theory in discussing the relationship between hosts and tourists to explain tourists' loyalty towards homestay industry.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Second, this study found that the experiential consumption and the social environment perceived by the tourist and involvement in the experience are essential components for tourists, which inform their intention to return to the guesthouse. Preceding researchers have shown that tourists' decision to revisit a specific place is largely based on their satisfaction [75] regarding this place during their previous visits, but our research has shown that their decision also depends on the involvement that a client may experience during their experience in a guesthouse. Hence, it is necessary that managers aim to involve their tourists by fostering long-term collaborative relationships with them, as well as offering them new and distinctive experiences.…”
Section: Discussionmentioning
confidence: 75%
“…The results presented in Table 4 demonstrate an adequate discriminant validity founded on both approaches. In the second step, we recognized the values of experiential consumption and the social environment as secondorder formative constructs applying the score of their correlated dimensions from the first step [75]. Utility, social connection, knowledge, escape, experiential stimulation, and spiritual value established the value of experiential consumption [23,76], while enchantment and hospitality established the concept of the second-order social environment.…”
Section: Assessment Of Measurement Modelmentioning
confidence: 99%
“…Pandemic-related uncertainty spawned marketing concerns that inspired innovations as the hospitality industry adopted advertising channels such as TikTok ( Altinay & Arici, 2021 ). However, most bookings were still completed via OTAs; tourism entrepreneurs and tourists alike deem these sites trustworthy and reliable ( Wang et al, 2020 ). Available marketing channels also afforded entrepreneurs opportunities to choose the most appropriate platforms to raise awareness of their businesses, representing an incremental marketing innovation ( Huang & Farboudi Jahromi, 2021 ).…”
Section: Resultsmentioning
confidence: 99%